Who Seeks Treatment When Medicine Opens the Door to Pathological Gambling Patients—Psychiatric Comorbidity and Heavy Predominance of Online Gambling - Håkansson, Anders; Mårdhed, Emma; Zaar, Mats (Frontiers in Psychiatry, 2017)
Background: Few studies have assessed treatment-seeking behavior and patient characteristics in pathological gambling focusing on psychiatric co-morbidity, particularly in a setting of heavy exposure to online gambling. The present study aimed to address patient characteristics in a novel health care-based treatment modality for pathological gambling, including potential associations between gambling types, psychiatric co-morbidity, and gender. Methods: All patients undergoing structured assessment between January, 2016 and April, 2017, were included (N=106), and patient records were reviewed for co-occurring psychiatric disorders and types of problem games. Results: Eighty percent were men, and 58 percent received a psychiatric disorder apart from pathological gambling. Problematic gambling on online casino and online sports betting represented 84 percent of patients. Non-substance-related psychiatric co-morbidity was significantly associated with female gender. Conclusion: Online gambling is more clearly predominating in the present setting than in studies from other countries. High rates of co-morbidity call for structured psychiatric assessment in problem gambling, with a particular focus on female patients with pathological gambling.